Unlocking the potential of digital twins in supply chains - Tozanli, Özden; Saénz, Maria Jesús (MIT Sloan Management Review, 2022)
Digital twins — virtual replicas of physical entities and their interactions — are often poorly understood, which has led to their underutilization in supply chain management. The authors offer several examples of companies that have successfully used digital twins to enhance their supply chains, and they describe the main functional areas where leading companies have harnessed the technology: supply chain planning, warehouse management, and transportation management and last-mile delivery.